Radiotherapy and the Tumor Stroma: The Importance of Dose and Fractionation - Hellevik, Turid; Martinez-Zubiaurre, Inigo (Frontiers in Oncology, 2014)
Ionizing radiation (IR) is a non-specific but highly effective way to kill malignant cells. However, tumor recurrence sustained by a minor fraction of surviving tumor cells is a commonplace phenomenon caused by the activation of both cancer cell intrinsic resistance mechanisms, and also extrinsic intermediaries of therapy resistance, represented by non-malignant cells and structural components of the tumor stroma. The improved accuracy offered by advanced radiotherapy (RT)-technology permits reduced volume of healthy tissue in the irradiated field, and has been triggering an increase in the prescription of high-dose oligo-fractionated regimens in the clinics. Given the remarkable clinical success of high-dose RT and the current therapeutic shift occurring in the field, in this review we revise the existing knowledge on the effects that different radiation regimens exert on the different compartments of the tumor microenvironment, and highlight the importance of anti-tumor immunity and other tumor cell extrinsic mechanisms influencing therapeutic responses to high-dose radiation.